Analisis Literatur tentang Restorative Justice: Tinjauan Terhadap Implementasi dan Dampaknya - Robby Kartika Putra, Aulia (Jurnal Ilmiah Wahana Pendidikan, 2024)
This research aims to analyze the implementation and impact of restorative justice within Indonesia's criminal justice system. The background of this study is the need to adapt criminal law to the increasingly complex developments of society. The concept of restorative justice emphasizes the restoration of relationships between offenders, victims, and the community, contrasting with the retributive approach focused on punishment. The research methodology employs a qualitative approach with a juridical-normative focus, consisting of a literature study with descriptive-analytical analysis. Data were collected from five journals discussing restorative justice and various other legal sources. The findings reveal that restorative justice has significant potential to create a more humane, inclusive, and efficient judicial system in Indonesia. Appropriate policy support and commitment from all related parties are crucial for the successful implementation and impact in the future.